A Review of Islamic Criminal Law on Non-Penal Policies in Combating Sexual Violence in Banda Aceh City - Mayasari, Seva; Azizah, Noor (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The crime of sexual violence arises from the intention and opportunity of the perpetrator due to the lack of conditions that provide legal protection for the victim. Therefore, it is important to carry out policies and preventive measures before the crime of sexual violence occurs. This research focuses on non-penal policies, namely policies that are more preventive. This study aims to examine the review of Islamic criminal law in looking at the non-penal policies that have been carried out by the Banda Aceh City Government in overcoming sexual violence. The research method used in this study is empirical legal research with a sociological approach and the main data source is the policy carried out by the Banda Aceh City Government, in terms of tackling sexual violence, then the data obtained from the field will be seen in the perspective of Islamic criminal law. As for the results of this research, many efforts have been made to minimize the occurrence of sexual violence crimes in the city of Banda Aceh. Among them, there is the role of the Pamong Praja Police Unit (Satpol PP) and the Wilayatul Hisbah Police Unit in enforcing qanun, as well as the appointment of Muhtasib Gampong personnel. In addition, the Banda Aceh City Government also issued a Mayor's Circular Letter containing an appeal to wear Muslim/Muslim women's clothing, and the Islamic Sharia Office through the Da'wah Field routinely runs programs in the context of overcoming sexual violence. The various non-penal policies implemented by the Banda Aceh City Government are basically in line with the principles required by Islamic law, and can be categorized as part of the provisions of taʿzīr. However, based on the understanding of the Qur'an and Hadith, Islamic criminal law essentially emphasizes preventive aspects that are rooted in people's personal awareness, such as maintaining views, regulating associations, controlling lust, and other behaviors that can prevent offenses.